Key ideas in criminology and criminal justice - Pratt, Travis C.; Gau, Jacinta M., 1982-; Franklin, Travis W.; Sage eBooks (Los Angeles : SAGE, 2011)
The development of both criminology and criminal justice has been characterized by different theories and ideas that capture academic (and sometimes political) imaginations and send the discipline veering in entirely new directions. Why did these ideas catch on? What about them attracted and held scholars' attention and on occasion caused them to impact policy considerations? Why do they still have value today? These are the questions addressed in 'Key Ideas in Criminology and Criminal Justice'.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Criminology; Criminal justice, Administration of; Electronic books